2005
DOI: 10.3171/jns.2005.102.s_supplement.0119
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of gamma knife surgery for growth hormone—producing pituitary adenoma: is the disease difficult to cure?

Abstract: Gamma knife surgery was effective and safe for the control of tumors; however, normalization of GH and IGF-1 secretion was difficult to achieve in cases with large tumors and low-dose radiation. Gamma knife radiosurgery is thus indicated for small tumors after surgery or medication therapy when a relatively high-dose radiation is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Despite the proximity of the optic apparatus to the pituitary gland, only 10 case series 5,7,13,17,18,25,32,44,58,62 in our analysis reported postradiosurgical visual complications, with Kobayashi et al 25 demonstrating the highest incidence at 11%. The low rate of visual complications following SRS likely stems from each group's attempt to limit the dose received by the optic apparatus to 8-10 Gy.…”
Section: Adverse Effectsmentioning
confidence: 54%
See 2 more Smart Citations
“…Despite the proximity of the optic apparatus to the pituitary gland, only 10 case series 5,7,13,17,18,25,32,44,58,62 in our analysis reported postradiosurgical visual complications, with Kobayashi et al 25 demonstrating the highest incidence at 11%. The low rate of visual complications following SRS likely stems from each group's attempt to limit the dose received by the optic apparatus to 8-10 Gy.…”
Section: Adverse Effectsmentioning
confidence: 54%
“…Thus, unlike the optic apparatus, which is especially sensitive to radiation dosing, the structures traversing the cavernous sinus appear more resistant to injury. 50,56 Kobayashi et al 25 reported postradiosurgical visual complications in 11% of the 67 patients with acromegaly in their study, yet new-onset optic neuropathies were only noted in a total of 10 case series in our review of the literature. To minimize damage to the optic apparatus, many groups attempt to limit the dose it receives to 8-10 Gy.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…1,2,7,10,13,14,18,24,26,[29][30][31]33) Descriptions of the endocrine and radiographic outcomes of GKRS for GH-secreting adenomas are summarized in Table 2. In these studies, the mean follow-up periods ranged from 35 to 120 months.…”
Section: Gh-secreting Adenomas I Gamma Knifementioning
confidence: 99%
“…5 One of the challenges for surgery and radiation is the close proximity of the pituitary adenoma to critical structures, such as the optic and abducens nerves and internal carotid arteries, 13 with reported visual side effects and cranial nerve palsies in up to 11% of patients. 14,15 Tumor-specific radiosensitizers could improve the therapeutic window of radiation therapy, and decrease adverse effects while improving efficacy.…”
Section: Introductionmentioning
confidence: 99%